Histopathological Appearance of Parakeratinized Odontogenic Keratocyst - Pylkkö, Jaakko (My University, 2021)
Introduction: Odontogenic keratocyst (OKC) typically grows locally aggressively and recurrence is common. The purpose of this study was to evaluate the clinical pathological features of OKC and to compare them with the behavior of OKC. Materials and methods: A total of 226 cases of OKC was identified in 174 patients over 36 years period in a single institute in South-western Finland. Histological specimens were re-evaluated, and case data were collected from the pathological-anatomical diagnosis (PAD) and their referrals. Patients' age, sex, location of OKC, recurrency and histopathological features were compared in relation to each other. Results: The majority of subjects were men (1.28:1), with a mean age of 46.16 years and the most typical site of occurrence was the lower jaw (77.1%). With a total of 21.3%, OKC recurred. With histopathological analysis, cyst epithelium was uniform in thickness (169/174, 97.1%), and detachment from connective tissue occurred in 64.6% of the samples. Inflammation was present in 95% of the samples. Satellite cysts occurred in 9.7% of cases. In patients diagnosed with satellite cysts, OKC recurred in 50% of the cases while without satellite cysts only 16.7% recurred (p=0.001). Conclusion: Compared to the literature, patient material in this study was, on average, older and cysts were found more frequently as inflamed. Satellite cysts occurred only in association with inflammation. Based on the results, regular radiographical evaluation is important in the second and third decades, to detect OKCs and to treat them before enlargement, infection, and inflammation. Histopathologically, the appearance of satellite cysts in the OKC should be reported and may be a sign of an increased risk of OKC renewal.

Tausta: Odontogeeninen keratokysta (OKC) tyypillisesti kasvaa paikallisesti aggressiivisesti ja uusiutuvuus on yleistä. Tämän tutkimuksen tarkoituksena oli arvioida OKC:n kliinispatologiset piirteet ja verrata niitä OKC:n käyttäytymiseen Varsinais-Suomalaisessa aineistossa. Aineisto ja menetelmät: Yhteensä 36 vuoden aikana 174 potilaalta todettiin 226 OKC tapausta. Histologiset leikkeet arvioitiin uudelleen WHO:n (2017) ohjeistusten mukaisesti ja tapausten tiedot kerättiin patologis-anatomisesta tutkimuksesta (PAD) ja niiden lähetteistä. Potilaiden iän, sukupuolen, OKC:n sijainnin, uusiutumisen ja histopatologisten ominaisuuksien ilmenemistä verrattiin suhteessa toisiinsa. Tulokset: Potilaista suurin osa oli miehiä (1,28:1). Keski-ikä oli 46,2 vuotta ja OKC:n tyypillisin esiintymispaikka oli alaleuassa (77,1 %). Potilaista 21,3 %:lla OKC uusiutui. Histopatologisessa tutkimuksessa kystaepiteeli oli pääsääntöisesti tasapaksua (169/174, 97,1 %). Epiteelin irtoamista sidekudoksesta esiintyi 64,6 %:ssa näytteistä. Näytteistä 95 %:ssa esiintyi tulehdusta. Satelliittikystia esiintyi 9,7 % tapauksista. Potilailla, joilla esiintyi satelliittikystia, 50 %:lla OKC uusiutui, kun ilman satelliittikystia uusiutuminen oli 16,7 % (25/150) (p=0.001). Johtopäätelmä: Tutkimuksen tulokset tukevat suurimmilta osin aiempia löydöksiä kirjallisuudessa. Eroavaisuudet olivat, että potilasmateriaalimme oli keskimäärin hieman vanhempaa ja kystat löytyivät useammin tulehtuneina. Satelliittikystia esiintyi vain tulehduksen yhteydessä. Tulosten perusteella säännöllinen panoraamatomografia-kuvaus on suositeltava etenkin toisen ja kolmannen vuosikymmenen ikäisillä henkilöillä, jotta OKC:t löydettäisiin ja hoidettaisiin ennen laajenemista ja tulehtumista. Satelliittikystien näkyminen histologisesti OKC:ssä olisi syytä raportoida ja se voi olla merkki lisääntyneestä riskistä OKC:n uusimiselle.
Keywords: Odontogenic keratocyst, histopathology, keratocystic odontogenic tumor, parakeratinization, histological appearance, recurrence